Clinical Trials in Vulnerable Populations 2018
DOI: 10.5772/intechopen.70188
|View full text |Cite
|
Sign up to set email alerts
|

Training Programs for Improving Communication about Medical Research and Clinical Trials: A Systematic Review

Abstract: Objectives: The aim of this article is to provide recommendations on the structure, materials, and outcomes that should be adopted for communication training programs designed to improve clinical trial education for patients. Methods:A systematic review of peer-reviewed articles was conducted. A total of 22 studies were included. Several dimensions were analyzed, such as program design, content development, pedagogical tools, content of the program, and the outcomes affected. Results:The trainings described in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Communication in a clinical research setting is primarily done to book participants for their visits, and to communicate with participants about their progress in the studies. 2 Morgan et al 3 reported that communication is crucial to ensure that recruitment, enrolment and retention of participants are successful. Verbal and non-verbal communication styles also influence the success of a clinical trial.…”
Section: Introductionmentioning
confidence: 99%
“…Communication in a clinical research setting is primarily done to book participants for their visits, and to communicate with participants about their progress in the studies. 2 Morgan et al 3 reported that communication is crucial to ensure that recruitment, enrolment and retention of participants are successful. Verbal and non-verbal communication styles also influence the success of a clinical trial.…”
Section: Introductionmentioning
confidence: 99%
“…Current assessments of the quality of communication practice as an outcome of clinical trial communication training has focused on several tools: (1) surveys of training participants' knowledge, attitudes, and perceived self-efficacy; (2) role-plays to practice skills; (3) videotaping participants to provide individualized feedback, and (4) the use of check lists to assess recruiters' behaviors when interacting with potential participants [18]. While all of these assessment strategies are valuable, none of these approaches has been validated, including the self-report survey, which is the most commonly used tool [18]. The development and evaluation of more effective training programs depend heavily on the use of validated and, preferably, triangulated outcome measures.…”
Section: While Clinical Trial Communication Training Programsmentioning
confidence: 99%
“…Just as public speaking abilities can be developed through professional training, the specific interpersonal verbal and nonverbal practices that foster positive interactions with Clinical Trials in Vulnerable Populations patients in a clinical trial recruitment context can be taught [17]. The content of clinical trial communication training programs varies considerably (as do outcomes), but most programs appear to be successful in improving the confidence of those who recruit for studies [18].…”
Section: Introductionmentioning
confidence: 99%